Entrepreneurship: Origin, Returns, and the Role of School Choice in Youth Entrepreneurship - Rahman, Haji; Ahmad, Fawad; Marwat, Imran Ullah (The Lighthouse Journal of Social Sciences, 2023)
Entrepreneurship is the ability of a person to become an initiator of a new business, a new product, or a new process within an existing business. Entrepreneurs bring a novel dimension to an existing business or an existing product. Entrepreneurs invest financial and human capital in the business and expect more returns than they spend. This is one of the most important contributions of humans, which brings prosperity, development, and success to human life in an individual capacity, at the societal level, and at the national/country level. This paper is an exploratory research based on the existing literature and qualitative primary data, hence examines the origins of entrepreneurship, its return or outcome, and the role of school and academic programs in motivating them toward entrepreneurship. The influential factors include occupational qualification, family background, gender, academic institutions, work environment, unemployment threat of downsizing, teacher role, and the environment of the schools. The findings provide guidelines for the policymakers and individuals on how to pursue the potential life and make it more productive for themselves and the national prosperity through providing a conducive school and academic institutions environment. Hence it is recommended to the responsible authority of the educational institutions to introduce such programs in the academia at large, which could motivate and guide them on how to become successful entrepreneurs and intrapreneurs.